Ganglion blocks as a treatment of pain: current perspectives - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2017)
The inputs from sympathetic ganglia have been known to be involved in the pathophysiology of various painful conditions such as complex regional pain syndrome, cancer pain of different origin, and coccygodynia. Sympathetic ganglia blocks are used to relieve patients who suffer from these conditions for over a century. Many numbers of local anesthetics such as bupivacaine or neurolytic agents such as alcohol can be chosen for a successful block. The agent is selected according to its duration of effect and the purpose of the injection. Most commonly used sympathetic blocks are stellate ganglion block, lumbar sympathetic block, celiac plexus block, superior hypogastric block, and ganglion Impar block. In this review, indications, methods, effectiveness, and complications of these blocks are discussed based on the data from the current literature.
Keywords: cancer pain; complex regional pain syndrome; ganglion; pain management; sympathetic nervous system; CELIAC PLEXUS BLOCK; UNRESECTABLE PANCREATIC-CANCER; CLASSIC POSTERIOR APPROACH; ACUTE HERPES-ZOSTER; QUALITY-OF-LIFE; ENDOSCOPIC ULTRASOUND; SPHENOPALATINE GANGLION; DOUBLE-BLIND; SYMPATHETIC BLOCK; NERVE BLOCKS